INTEGRATING ENGLISH INSTRUCTIONAL TECHNOLOGY TO EMPOWER STUDENTS’ READING COMPREHENSION - Ira Irzawati; Yunani Atmanegara (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The integration of technology into English Language Teaching (ELT) has been developed recently. Many studies revealed that the impacts of English instructional technology can enhance the students’ English learning achievements. However, there are some problems that need more concern from educators.One of them is reading comprehension as it is one of the crucial skills in National Examination in Indonesia. To empower students’ reading comprehension, the successful integration of English instructional technology into ELT could be the solution to cope with it. In this study, Webquest is an instructional technology tool used to increase students’ reading comprehension achievements. Sixty two of senior high school students were involved as participants of this study. By conducting experimental research, thirty-one students were in the experimental group and the others were in the control group. The results revealed that the experimental group achieved higher scores than the control group. It indicates that Webquest is effective to improve students’ reading comprehension achievements. In a nutshell, the implementation of technology in ELT could empower students’ reading comprehension. Key words: English instructional technology, reading comprehension, Webquest